Efficient liquefaction of woody biomass in polyhydric alcohol with acidic ionic liquid as a green catalyst. (October 2015) - Lu, Zexiang; Fan, Liwei; Wu, Zhengguo; Zhang, Hui; Liao, Yiqiang; Zheng, Deyong; Wang, Siqun
Abstract: The catalytic performance of acidic ionic liquids (AIL) containing HSO 4 − anion and acidic-functionalized imidazolium cations for biomass liquefaction was firstly investigated in polyethylene glycol 400-glycerol mixture at atmospheric pressure in order to explore green and efficient ways to convert woody biomass into sustainable energy and chemicals. The results showed that fir sawdust (10 g) was up to 99% liquefied using 60 g of solvent at a concentration of 1-(3-sulfopropyl)-3-methylimidazolium hydrogensulfate ionic liquid of 0.3 mol·L −1, at a temperature of 423 K, in 60 min. The introduction of the sulfoalkyl substituent into the imidazolium cation of AILs was found to significantly improve their catalytic activity. The catalytic performances of 1-(3-sulfopropyl)-3-methylimidazolium hydrogensulfate and 1-(4-sulfobutyl)-3-methylmidazolium hydrogensulfate are thus similar to that of H2 SO4 due to their double acidic sites. More than 90 wt% of the bio-oil was the heavy oil that derives from lignin. Highlights: A series of acidic ionic liquids (AILs) as green catalysts were synthesized. The AILs was firstly applied to the liquefaction of sawdust in PEG 400/glycerol. The sulfoalkyl substituent of AILs improves their catalytic activity. The catalytic property of [BsMIM]HSO4 ionic liquid is similar to that of H2 SO4 .